Synthetic Studies Toward the Citrinadin A and B Core Architecture - Mundal, Devon A. (2013)
[Image: see text] The core architecture of the citrinadin alkaloids has been prepared in racemic form by utilizing a strategy that exploits the alkylation of 2-methoxypyridines. An initially planned indolizidine to quinolizidine transformation to build the D/E rings was unsuccessful. Success was ultimately gained by a direct alkylation to establish the citrinadin core architecture.